Suspected or known neonatal sepsis and neurodevelopmental delay by 5 years. (November 2018) - Savioli, Katrina; Rouse, Christopher; Susi, Apryl; Gorman, Gregory; Hisle-Gorman, Elizabeth
Abstract Objective Evaluate impact of known and suspected neonatal sepsis in the term and preterm infant on neurodevelopmental delay by 5 years. Study Design Included infants were born in 2009–2010 and followed for 5 years. Diagnostic codes and at least 5 days of antibiotic use identified suspected sepsis. Laboratory results confirmed known sepsis. Diagnostic codes stratified developmental delay by sub-type. Logistic regression analysis determined odds of developmental delay for sepsis and suspected sepsis. Results Of 65, 938 included infants, 190 had sepsis and 3449 had suspected sepsis. After adjustment for known developmental risk factors, sepsis and suspected sepsis were associated with increased risk for any developmental delay, (1.48 (1.05–2.09) and 1.09 (1.01–1.18)), respectively, and multiple developmental delay sub-types. Conclusion Neonatal sepsis and suspected sepsis are associated with neurodevelopmental delay by 5 years of age.